Antibacterial Activity of Rosemary Oil Against Propionibacterium acnes and The Formulation into Nanoemulsion System - Sani Ega Priani; Rizza F. Nurasyfa; G.C. Eka Darma; Sri P. Fitraningsih; Livia Syafnir; Robby Prayitno (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Acne is an inflammatory condition of the pilosebaceous unit that can occur due to infection ofPropionibacterium acnes. Rosemary essential oil contains various active compounds that haveantibacterial activity. Nanoemulsions have been developed as a delivery system to the pilosebaceousunit. This study aimed to determine the antibacterial activity of rosemary oil against P. acnes anddevelop it into a nanoemulsion system. The antibacterial activity was conducted by the agar diffusionmethod. Rosemary oil contains 1,8-cineole as the main active compound and has antibacterial activityagainst P. acnes with an inhibitory zone of 11.315±0.069 mm at a concentration of 4%. Rosemaryoil was successfully developed into a nanoemulsion system using Tween 80 as a surfactant and acombination of ethanol and PEG 400 as a co-surfactant. The rosemary nanoemulsion has a clearphysical appearance with an average globule size of 33.50±0.01 nm and a PDI value of 0.45±0.03. Thepreparation has good physical stability based on centrifugation, heating cooling, and freeze-thaw tests.The study shows that rosemary oil has antibacterial activity against P. acnes and has been successfullydeveloped into nanoemulsion preparations with good characteristics and physical stability. Keywords: Acne vulgaris, Nanoemulsion, Propionibacterium acnes, Rosemary oil.